Ensuring That Regulations Evolve as Mini Grids Mature - World Bank Group (World Bank, Washington, DC, 2019)
As they mature, mini grid sectors evolve from marginally viable competitive entrants to potential monopoly providers of essential services. In early stages, overly stringent regulation can choke the sector’s growth. In later stages, however, closer regulation is usually necessary to protect customers. Regulators can manage the regulatory evolution required of this sector by defining its growth phases and spelling out, in advance, the regulations that will apply at each stage.